2017
DOI: 10.1016/j.beproc.2017.02.018
|View full text |Cite
|
Sign up to set email alerts
|

Brood size can influence maternal behaviour and chick’s development in precocial birds

Abstract: Mothers have a crucial influence on offspring development. Variations of maternal behaviour can be due to numerous parameters, for instance costs are related to the size of a brood/litter, which in turn can influence the level of mothers' investment in each offspring. Here we investigated the influence of brood size on the behaviour of Japanese quail mothers and chicks during the mothering period and on offspring development. We compared two types of broods: small broods of three chicks (N=9) and large broods … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
8
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 54 publications
1
8
0
Order By: Relevance
“…Our results on maternal behavior were consistent with previous studies (Aigueperse et al, ; Pittet, et al, ). It was, therefore, relevant to correlate this behavior with chick development.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Our results on maternal behavior were consistent with previous studies (Aigueperse et al, ; Pittet, et al, ). It was, therefore, relevant to correlate this behavior with chick development.…”
Section: Discussionsupporting
confidence: 93%
“…In altricial birds, parents have been found to provide for their chicks more or less according to their sex (Stamps, Clark, Kus, & Arrowood, ; Weimerskirch, Barbraud, & Lys, ). Recently, we have demonstrated that maternal foster quails interact differently according to chicks’ sex, and are closer to their male chicks than to their female ones (Aigueperse et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…We also showed that adoptive mothers rejected less chicks from stressed females. Previous studies demonstrated that quail mothers present, between PHD5 and PHD7, an "emancipatory rejection" behaviour, which stimulates chicks' independence (Aigueperse et al, 2017): mothers reject their chicks and become more aggressive when their chicks insistent on remaining close A u t h o r ' s p r e -p r i n t to their mother. Here, we found a similar pattern for NPS-m mothers but not for PS-m mothers that never expressed this "emancipation rejection" during the 11 days of the mothering period and appeared to stimulate their chicks' independency only later.…”
Section: Discussionmentioning
confidence: 99%
“…For example, in Japanese quail ( C. japonica ), mothers of large broods emitted more maternal vocalisations at the start of mothering but covered the young less towards the end. Chicks in turn huddled more and had higher social motivation than chicks in small broods (Aigueperse et al 2017 ). Impaired maternal care (Champagne et al 2003 ; Lindeyer et al 2013 ), which may in turn be caused by poor habitat conditions (Ivy et al 2008 ), and maternal stress (Rooke et al 2017 ) have also been empirically linked to the development of coping behaviours.…”
Section: What In the Early-life Environment Affects Later-life Copingmentioning
confidence: 99%